Avalia????o da aprendizagem educa????o superior: um estudo sobre as concep????es dos professores da Universidade Federal do ABC - Galocha, Carlos (2019)
This research has as object of study the evaluation of learning in higher education, specifically in the Federal University of ABC (UFABC) Santo Andr?? campuses, as a universe of research. The research question results from the problem related to the fact that this university has been a higher education institution to constitute itself as a new educational model in relation to traditional higher education institutions. In this sense, we intend to know how the professors put into practice the assessment of the learning of the students at that university, considering their conceptions and the epistemological and pedagogical principles contained in the documents that guide the institution. We analyze the evaluative processes and models used by teachers. A qualitative methodological approach is adopted, as a resource for the study of institutional documents and semi-structured interviews. Interviewees are members of the faculty at UFABC's interdisciplinary bachelor's degree course in science and technology. The conjecture that guided this work is that the new model of higher education proposed in the documents of the institution under study brings some changes in the traditional way of assessing student learning. The interviews were analyzed according to the discourse analysis technique, based on the foundations of Eni Pucinnelli Orlandi. The final considerations indicate that the UFABC adopts a model of higher education, sustained by its main structural axes: social inclusion, academic excellence and interdisciplinarity. Regarding the assessment of learning, the institution has assessment concepts according to its guiding documents, but the continuity of the traditional form of assessment was observed. The teachers' discourse analysis shows that the evaluative practice, despite being expressed in a conceptual form, doesn???t innovate in order to review the evaluation paradigms. Of the interviewees, only two subjects adopt a continuous process of evaluation (diagnostic, formative and summative), the others are worth of assessments without reference and others are based on Hoffmann as theorist. We also find in the speeches that interdisciplinarity has as a factor of difficulty the traditional training of most of its teachers.